2005
DOI: 10.1002/cbic.200400421
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Evaluation of Antioxidant and Pro‐oxidant Activities of Polyphenols with Thymidine Protection Assays

Abstract: A recently reported high-throughput screening strategy has been applied to the rapid selection of new water-soluble antioxidants that display strong protective activities. Based on a competitive immunoassay, a triple-screening procedure was used to evaluate the ability of different compounds to protect thymidine under different oxidative stresses. The pro-oxidant effect of norbadione A in the presence of iron was observed, while some pulvinic acid derivatives proved strongly protective during gamma radiolysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
1
35
0
2
Order By: Relevance
“…27 Firstly, the protection of thymidine towards three types of oxidative conditions (c-rays, UV/H 2 O 2 , and Fenton oxidation) was determined using the previously described immuno-enzymatic assay. 10,13 Then, the radical scavenging properties of the compounds were studied using assays based on two oxidants, the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH Å ) and the radical cation of (2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS Å+ ). Finally the evaluation of b-carotene protection in a lipidic emulsion under oxidative conditions by the compounds was realized.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Firstly, the protection of thymidine towards three types of oxidative conditions (c-rays, UV/H 2 O 2 , and Fenton oxidation) was determined using the previously described immuno-enzymatic assay. 10,13 Then, the radical scavenging properties of the compounds were studied using assays based on two oxidants, the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH Å ) and the radical cation of (2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS Å+ ). Finally the evaluation of b-carotene protection in a lipidic emulsion under oxidative conditions by the compounds was realized.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…However, this product was found to be inefficient towards another oxidative stress, the Fenton-type oxidation, which was instead rather typical of a pro-oxidant activity. 13 Further studies showed that a structurally related pigment, di-O-methylatromentic acid (2), efficiently protected thymidine towards the three stress conditions, and did not show any pro-oxidant behavior. Compound 2 belongs to a larger pigment family typical of boletes, and also found in lichens, pulvinic acids, the simpler of which is pulvinic acid (3).…”
Section: Introductionmentioning
confidence: 99%
“…They have been demonstrated to function as antioxidants in vitro both in cell cultures and cell-free systems by scavenging superoxide anion, singlet oxygen, lipid peroxy-radicals, and/or stabilizing free radicals involved in oxidative proc-esses through hydrogenation or complexing with oxidizing species [3,18,19]. However, in vitro experiments reported that most of dietary compounds with therapeutical properties act as potent pro-oxidants molecules [20,21] at high concentrations or in presence of transition metals [22]. This pro-oxidant effect increases reactive oxygen species (ROS) production which, acting as second messengers of signaling networks, may induce growth arrest and apoptosis [23].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have indicated that some nutraceuticals exhibit potent anti-tumor properties and can modulate apoptosis, differentiation and cell cycle, probably by virtue of their anti-oxidant functions. However, in vitro experiments reported that most of them behave as potent pro-oxidants molecules [6,9,40]. For example, organosulfur molecules from garlic, such as the oil-soluble diallyl disulfide [12,13], diallyl trisulfide [22], or the water-soluble S-allylmercaptocysteine [63] have been demonstrated to induce growth arrest and apoptosis dose-dependently by increasing ROS production.…”
Section: Introductionmentioning
confidence: 99%